Hinduism's four stages of life in Saul Bellow's Henderson the Rain King - Mani, Manimangai (Australian International Academic Centre, 2016)
The oldest of Hindu’s philosophical writings, the Rig Veda, which came to being about 4500 BC underlined that, the cause of all misery that befalls mankind is his/her desire; or more promptly said, his/her attachment to the desire. In Hinduism, this physical plane is just a stage with life itself is nothing more than a play. The stage is set in such a way to enable the souls which took the human form to evolve and to find the enlightenment and ultimately to become one with the creator. All the material elements including the complex relationship found in this plane is nothing but a mere illusion. This study aims to explore elements of Hindu philosophy in Saul Bellow’s novel, Henderson the Rain King (1976). Eugene Henderson, the main character in this novel is portrayed as drowning in the materialistic world. Being constantly mugged by a desirable voice within him whispering, I want, I want, it is not an irony if he generated a sense of uselessness and emptiness. This study shows how Henderson’s decision to go to Africa to find the meaning of life coincides with the Hindu philosophy of the four stages of life; Brahmacharya (celibacy), Grahasthya (householdership), Vanaprastha (detachment in attachment) and Sanyas (seclusion). Henderson comes to realization in his third stage and proceeds to the fourth stage. Henderson is taught to eradicate fear and to break the cycle of desire. Towards the end, Henderson realises that the voice was actually referring to, “He wants, She wants and They want”. The voice was actually echoing the desires of mankind.